Telehealth‐guided home‐based maggot debridement therapy for chronic complex wounds: Peri‐ and post‐pandemic potential. Issue 5 (18th June 2020) - Armstrong, David G.; Rowe, Vincent L.; D'Huyvetter, Karen; Sherman, Ronald A.
Abstract: Patients with complex chronic lower extremity wounds require a great deal of interaction with outpatient and inpatient services. Paradoxically, these are the very patients that, because of their chronic comorbidities, are at greatest risk for COVID‐related morbidity and mortality. Disinfected Phaenicia ( Lucilia ) sericata (Medical Maggots; Monarch Labs, Irvine, California) were applied in a standardised fashion by a home‐health nurse with direct monitoring, guidance, and collaboration of the attending surgeon. A family member was able to change the outer dressing daily based on normal wound exudate. The inner maggot debridement therapy (MDT) dressing was changed at 2 days showing dramatic reduction in necrotic tissue, elimination of profound malodor, and no evidence of local or advancing infection. The entire initial telehealth‐guided application took approximately 20 minutes. The first telehealth‐guided MDT dressing change took 14 minutes. We used an artificial‐intelligence‐based algorithm to measure changes in wound characteristics. At day 0, 46% of the total surface area was covered in malodorous black, necrotic tissue. The first dressing change saw an elimination in assessed malodor with necrotic tissue constituting 14% of total surface area. The second dressing change at 5 days showed a greater than 99% reduction in necrotic tissue. This manuscript constitutes what we believe to be the first telehealth‐guided MDT conducted during a resource‐limited peri‐pandemic period. We believe that MDT, which is an extension of efforts regularly performed in clinic and hospital, may have the potential to reduce resource usage while potentially improving care and quality of life for people with limb and life‐threatening complications of diabetes and other chronic diseases.